Tentative Notes on a Two Sector Model with Induced Technical Progress - von Weizsacker, C. C. (Review of Economic Studies, 1966)
Journal Article Tentative Notes on a Two Sector Model with Induced Technical Progress Get access C. C. von Weizsäcker C. C. von Weizsäcker University of Heidelberg, Germany Alfred Weber Institut Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 3, July 1966, Pages 245–251, https://doi.org/10.2307/2974418 Published: 01 July 1966